O względności normy w zakresie ogólnopolskiej etykiety językowej - rzutowanie na sytuację języka polskiego na Ukrainie = On the relativeness of norms of Polish Language Etiquette: projecting on the situation of Polish language in Ukraine - Krawczuk, Ałła (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article discusses the issues of the contemporary Polish language etiquette which cause the biggest normative doubts among the users of Polish, and which sometimes are differently assessed by the Polish language norm authorities. The attempt to take the analysis of judgments and evaluations generates the material for reflecting on the normative status of some of the language etiquette phenomena implemented by the persons of Polish origin living in Ukraine.
Keywords: tożsamość; tożsamość aktywna; tożsamość pasywna; tożsamość deliberatywna; memetyka; identyfikacja; samoidentyfikacja; język; językoznawstwo; językoznawstwo polskie